2017
DOI: 10.1007/s00421-017-3607-z
|View full text |Cite
|
Sign up to set email alerts
|

Dose effects of New Zealand blackcurrant on substrate oxidation and physiological responses during prolonged cycling

Abstract: Seven-day intake of New Zealand blackcurrant extract demonstrated a dose-dependent effect on increasing fat oxidation during 120-min cycling at 65% [Formula: see text] in endurance-trained male cyclists.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
59
4

Year Published

2017
2017
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 34 publications
(67 citation statements)
references
References 40 publications
4
59
4
Order By: Relevance
“…We now report for the first time that intake of NZBC extract for 7 days increased whole-body fat oxidation during prolonged moderate-intensity cycling in endurance-trained females. Moreover, fat oxidation was 27% higher with NZBC intake compared to the placebo condition, which is higher than the ~ 21.5% increase in fat oxidation reported by Cook et al ( 2017 ) using the same exercise protocol and NZBC extract dose (600 mg day −1 , containing 210 mg anthocyanins). Although a direct comparison between males and females in the same study is yet to be made, our data suggest that short-term intake of NZBC extract is at least as potent for increasing whole-body fat oxidation during exercise in females as previously observed in males.…”
Section: Discussioncontrasting
confidence: 56%
See 3 more Smart Citations
“…We now report for the first time that intake of NZBC extract for 7 days increased whole-body fat oxidation during prolonged moderate-intensity cycling in endurance-trained females. Moreover, fat oxidation was 27% higher with NZBC intake compared to the placebo condition, which is higher than the ~ 21.5% increase in fat oxidation reported by Cook et al ( 2017 ) using the same exercise protocol and NZBC extract dose (600 mg day −1 , containing 210 mg anthocyanins). Although a direct comparison between males and females in the same study is yet to be made, our data suggest that short-term intake of NZBC extract is at least as potent for increasing whole-body fat oxidation during exercise in females as previously observed in males.…”
Section: Discussioncontrasting
confidence: 56%
“…Evidence for nutritional supplements to increase fat oxidation during exercise is predominantly derived from studies conducted in males, and therefore, the effects of these supplements in females is largely unknown. Recently, it has been reported in two studies that NZBC intake for 7 days augmented whole-body fat oxidation during cycling at 65% VO 2max in endurance-trained males (Cook et al 2015 , 2017 ), but whether a similar effect is apparent in females has not been investigated. We now report for the first time that intake of NZBC extract for 7 days increased whole-body fat oxidation during prolonged moderate-intensity cycling in endurance-trained females.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Ammar et al [131] showed that pomegranate juice lowered the perception of knee extensor soreness and attenuated the acute rise in specific markers of tissue damage [e.g., creatine kinase (CK), lactate dehydrogenase] 3 min after Olympic weight-lifting movements, and improved the recovery kinetics of these same markers 48 h after exercise. Blackcurrant has been studied for its effects on exercise performance [135, 136], substrate oxidation [137], and physiological measures, such as blood lactate level [135, 136, 138]. Only one study has tested the effects of BC on exercise-induced muscle damage, subjective ratings of muscle soreness, and inflammation post-exercise [133].…”
Section: Micronutrientsmentioning
confidence: 99%